NEWBET telemedicine platform for burn patients. - Reina-Tosina, J. (IEEE Transactions on information technology in biomedicine)
Problems detected in the current healthcare services for burn patients and emergency situations are taken into consideration in the development of a telemedicine platform, which is proposed. Taking as a reference the user requirements and the client-server architecture, a model of communications that allows a bidirectional exchange of information is reported. Special attention is focused towards the methodology applied and the design of a friendly user interface compatible with the current prevailing clinical protocols. The platform is based on a Microsoft Windows environment, and communications are implemented by using sockets.